An order to transfer the matrimonial home absolutely to one party after a divorce under the Malaysian law: is it just and equitable? - Ibrahim, Norliah (2007)
A matrimonial home occupies a very important place in one married life. Not only it becoming more common for the family to buy their own house, but in many cases the matrimonial home is the most substantial assets of the spouse. Thus, it is undeniable fact that typically, matrimonial home is a major asset, if not the only assets of the family. In pursuant to this, when the marriage breaks down, the parties will claim their share over the matrimonial home. There are few orders made by the court for the purpose of dividing the property including the order to transfer the matrimonial home to one spouse absolutely. Thus, the paper is trying to examine whether this order is just and equitable taking into account few factors inter alia that interest of the children and the willingness of the spouse to waive their share in other properties. This will include discussion on the relevant provision governing the division of the matrimonial property for non-Muslims in Malaysia and decided cases